Effect of condylar osteochondroma resection through an intraoral approach on the masticatory functions: a preliminary evaluation based on occlusion and temporomandibular joint functions. Issue 3 (April 2021) - Liu, K.; Xue, X.; Yu, J.; Abdelrehem, A.; Zhang, L.; Dai, J.; Wang, X.
Abstract: With this research, we aimed to evaluate the effect of condylar osteochondroma (OC) resection through an intraoral approach on the masticatory functions. Resection of condylar OC was carried out via an intraoral approach with the help of three-dimensional (3D) design, endoscope, and navigation system. The T-Scan III computerised occlusal analysis system was used to evaluate the occlusal force distribution, recorded at pre-treatment (T1) and post-treatment (T2) intervals. Records of the clinical examination of the temporomandibular joint (TMJ), including maximal interincisal opening, mandibular lateral and forward movements, were also collected. Ten patients with condylar OC were enrolled in this study. The difference of force distribution between bilateral occlusion was reduced in T2 compared with T1 (11.92% ± 4.41% vs 48.52 % ± 28.37%, p<0.05), indicating better occlusal force distribution obtained after surgery. There was no significant difference in functions of the TMJ, such as maximal interincisal opening, and mandibular lateral and forward movements between T2 and T1 (p>0.05). Accordingly, condylar OC resection through an intraoral approach would obtain a satisfactory occlusal balance with no impairment of the temporomandibular joint functions.